CRIMINALIZATION OF MEDICAL PERSONNEL FROM THE PERSPECTIVE OF LEGAL RULES APPLICABLE IN INDONESIA - Amsir Saidi, Lindawati (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The criminalization of medical personnel is a legal issue that continues to emerge as public legal awareness and medical disputes increase. In practice, not all medical consequences that harm patients can be classified as criminal acts. This article aims to analyze the phenomenon of the criminalization of medical personnel from the perspective of applicable legal regulations in Indonesia, by examining the criminal and health legal frameworks, the boundaries between medical risks and criminal acts, and legal protection efforts for medical personnel. The method used is normative legal research with a statutory and conceptual approach. The results show that Indonesian law essentially provides protection mechanisms for medical personnel. However, in practice, there is still a tendency to prematurely apply criminal law to medical incidents that should be resolved through ethical and civil mechanisms. Therefore, clear boundaries regarding criminalization are needed to ensure fair legal protection for medical personnel.